Case Report: Amelioration of severe metabolic dysfunction-associated steatohepatitis after switching from conventional GLP-1RAs to tirzepatide - Oe, Yuki; Omori, Takashi; Aimono, Eriko; Furukawa, Shin; Kitakawa, Hirohiko; Tateno, Masatoshi; Sakai, Kiyoshi; Cho, Kyu Yong (Frontiers in Endocrinology, 2025)
Metabolic dysfunction-associated steatohepatitis (MASH) has cardiometabolic risk factors, such as obesity and type 2 diabetes, and has been reported to have a potentially higher risk of mortality than conventional steatotic liver diseases. Liver fibrosis develops and can progress to cirrhosis and hepatocellular carcinoma. Although some antidiabetic agents have been reported to ameliorate the condition, no specific medical treatment has been developed to date. Tirzepatide is a dual glucose-dependent insulinotropic polypeptide and glucagon-like peptide-1 (GLP-1) receptor agonist (GLP-1RA) that has shown efficacy against MASH in some clinical trials. However, these trials were limited to those with mild-to-moderate fibrosis and their history of treatment was often unclear. Here, we report the case of a 50-year-old man with a 16-year history of diabetes. He demonstrated poor control of his diabetes with elevated liver enzymes. A liver biopsy was performed and he was diagnosed with steatohepatitis. Liraglutide was administered for 3 years but his liver function and glycemic control deteriorated gradually and a second liver biopsy was performed in 2023. The histological examination found cirrhosis and liraglutide was switched to tirzepatide. Over 6 months of administration of tirzepatide, the patient’s glycated hemoglobin and elevated liver enzyme levels improved. A third biopsy was performed, which showed a marked improvement in histology, with the amelioration of liver fibrosis. A diagnosis of steatotic liver disease was made. Although some previous studies had demonstrated an amelioration of liver fibrosis and an improvement in the prognosis of patients following GLP-1RA treatment, effective medications for patients with severe fibrosis or who are refractory to treatment with GLP-1RAs has not been identified to date. We reported a case with severe MASH whose condition had ameliorated by switching from conventional GLP-1RAs to tirzepatide.